FORMULASI DAN STABILITAS FISIKA KIMIA SEDIAAN KOSMETIK ANTIOKSIDAN FACIAL SERUM DARI EKSTRAK AIR BIJI KOPI HIJAU (Coffea canephora var. Robusta) - Anggreani, Poppy Ayu; Halim , Guntoro (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Serums are products that have a high concentration of active ingredients and aim to provide specific benefits to the skin. The main phenolic acid contained in this green coffee bean extract is chlorogenic acid which is known as a strong antioxidant compound. The purpose of this study was to determine the effect of hydroxy ethyl cellulose as a gelling agent, physical stability, antioxidant effects on serum preparations of green coffee bean extract (Coffea canephora var. Robusta). Serum preparations with green coffee bean extract concentrations FI (0.5%), F2 (0.8%) and F3 (1.0%). Physical stability and antioxidant tests were carried out on green coffee bean extract serum preparations (Coffea canephora var. Robusta) including organoleptic test, homogeneity test, pH test, spreadability test and viscosity test with temperature storage (2-8oC), temperature (20-25oC) and temperature 40oC. Data analysis on physical stability using Two Way ANOVA statistics and antioxidant tests were carried out by linear regression. The results of this study the concentration of green coffee extract serum preparation (Coffea canephora var. Robusta) with hydroxy ethyl cellulose as a gelling agent affects the viscosity of the serum preparation, where the higher the concentration of green coffee extract (Coffea canephora var. Robusta) the preparation has a high viscosity. Stability testing results obtained were homogeneous, the colour became more intense dark yellow and with a thick texture along with the high concentration used, the effect of temperature, and the duration of the preparation.